THE EFFECTS OF A PHYSICAL ACTIVITY PROGRAM ON BODY COMPOSITION AND PHYSICAL CONDITION IN THE OVERWEIGHT ADULT - Bianca Mădălina PAPP; Carmen ȘERBESCU; Tudor CACIORA; Adriana BAIDOG; Varodi Mihaela OLĂU (Editura Universităţii din Oradea, 2019)
The main purpose of the study is to analyse the effects of a physical activity programme on the body composition and physical condition of the overweight adult. Starting from the assumption that, with the decrease of the period of time available for physical activities combined with an erratic eating, the overweight/obesity phenomenon associated with increased risk factors for cardiovascular diseases has become an important issue which the contemporary society is facing. Therefore, the organised physical activity adapted to the needs of each individual seems to be the most viable solution for the improvement of the general health. The study has been carried out on two subjects, a 21 year old male and a 45 year old female, for a period of three months in which they followed a 60 minutes/day, 7 days/week physical activity programme, accompanied by minor changes in their eating habits. In order to establish the efficiency of the training programme, the subjects underwent a series of measurements with the purpose to determine their body composition and stamina both at the beginning, as well as at the end of the three months of physical activity. The results obtained prove that only through the introduction of an aerobic physical activity and muscle toning programme may the health and physical condition reported to the state of health be improved both at the young adult as well as in middle aged subject.